Annotated bird sighting list for fall 1999 compiled by Dennis Henrickson - Henrickson, Denniset al (1999)
An annotated list of birds sighted by Dennis Henrickson. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1999. Epson - sheet feed/flatbed